Filling the Blue Box: Mutuelles, Self-financing and Financial Services in the South of Haiti - Wilson, Kim; Burpee, Gaye (Tufts Archival Research Center, 2005)
In Haiti, many farmers lie beyond the reach of the formal banking system and MFIs. A powerful method of local financial intermediation, called mutuelles is helping to bridge the gap. Efficiently formed by local NGOs and church organizations, mutuelles are forces of social change. They also demonstrate financial discipline and could prove an interesting market for MFIs and banks seeking new customers for financial services.